Supplemental Figures and Information for "Contrasting histories of duplication and loss for metabolic pathway and floral development genes revealed in analyses of California poppy (Eschscholzia californica) genome sequence and expression atlas" - Annette Becker; Clemens Rössner; Justus Liebig University Giessen (My University, 2025)
Supplemental Figures and Information for "Contrasting histories of duplication and loss for metabolic pathway and floral development genes revealed in analyses of California poppy (Eschscholzia californica) genome sequence and expression atlas" "Supplemental_Multiple_Sequence_Alignments_and_Phylogenetic_Trees_for_Contrasting_histories_of_duplication_and_loss_for_metabolic_pathway_and_floral_development_genes_revealed_in_analyses_of_California_poppy_(Eschscholzia_californica)_genome_sequence_and_expression_atlas.txt" contains the following information compiled in a single text file: (i) Multiple Sequence Alignments (MSAs) of BIA and carotenoid biosynthesis and MADS family protein sequences generated with MAFFT (v7.490) (mafft --localpair --maxiterate 1000 --thread -1 --reorder x.fasta > yfasta) in *.fasta format. Sequences were retrieved from phytozome (https://phytozome-next.jgi.doe.gov/blast-search, accessed in early to mid 2024) and ICIPS-garden BLAST (http://134.176.27.173/blast/). (ii) Maximum likelihood phylogenies in *.newick-format generated with IQTREE2 (v2.0.7) with at least 3 bootstraps (iqtree -s x.fasta -nt AUTO -b 3 -con -allnni -safe). To access a certain MSA or tree use a text editor to search for the desired information in the header and you will find the coresponding MSAs and ML-trees. header format: pathway[MADS|Carotenoid|BIA] clade[name] type[tree|MSA] format[*.nwk|*.fasta] To generate *.fasta and *.newick files copy the block(s) of interest into a new *.txt file and save in the desired format. "Supplemental_Figure_Dotplots_of_different_Ranunculales_Genomes_for:Contrasting_histories_of_duplication_and_loss_for_metabolic_pathway_and_floral_development_genes_revealed_in_analyses_of_California_poppy_(Eschscholzia_californica)_genome_sequence_and_expression_atlas" contains Dotplots of the E. californica genome and other Ranunculales genomes retrieved from Phytozome (https://phytozome-next.jgi.doe.gov/) or NCBI (https://www.ncbi.nlm.nih.gov/). Dotplots were generated with GENESPACE (Lovell et al. 2022, https://doi.org/10.7554/eLife.78526). The Analysis plots genomes along the x and y axis and shows syntenic blocks and copies. "Supplemental_Ks_Plots_for:Contrasting_histories_of_duplication_and_loss_for_metabolic_pathway_and_floral_development_genes_revealed_in_analyses_of_California_poppy_(Eschscholzia_californica)_genome_sequence_and_expression_atlas.pdf" contains Ks plots generated with tree2GD (Chen et al 2022, https://doi.org/10.1093/bioinformatics/btac669) based on Ranunculales genomes mentioned above.
Keywords: Phylogenies; Multiple Sequence Alignment; Dotplot; Ks Plot; ddc:570; ddc:580